Deep characterization of human γδ T cell subsets defines shared and lineage-specific traits - Sanz, Marta; Mann, Brendan T.; Ryan, Paul L.; Bosque, Alberto; Pennington, Daniel J.; Hackstein, Holger; Soriano-Sarabia, Natalia (Frontiers in Immunology, 2023)
Under non-pathological conditions, human γδ T cells represent a small fraction of CD3+ T cells in peripheral blood (1-10%). They constitute a unique subset of T lymphocytes that recognize stress ligands or non-peptide antigens through MHC-independent presentation. Major human γδ T cell subsets, Vδ1 and Vδ2, expand in response to microbial infection or malignancy but possess distinct tissue localization, antigen recognition, and effector responses. We hypothesized that differences at the gene, phenotypic, and functional level would provide evidence that γδ T cell subpopulations belong to distinct lineages. Comparisons between each subset and the identification of the molecular determinants that underpin their differences has been hampered by experimental challenges in obtaining sufficient numbers of purified cells. By utilizing a stringent FACS-based isolation method, we compared highly purified human Vδ1 and Vδ2 cells in terms of phenotype, gene expression profile, and functional responses. We found distinct genetic and phenotypic signatures that define functional differences in γδ T cell populations. Differences in TCR components, repertoire, and responses to calcium-dependent pathways suggest that Vδ1 and Vδ2 T cells are different lineages. These findings will facilitate further investigation into the ligand specificity and unique role of Vδ1 and Vδ2 cells in early immune responses.